TERAPI SEL MONONUKLEAR DARAH TEPI VERSUS TERAPI STANDAR PADA LUKA KAKI DIABET: Tinjauan Pustaka Sistematis Dari Uji Coba Kontrol Acak - Zaenab Ashraf Abdallah (2021)
Backgorund: Diabetic foot ulcers (DFU) is one of the complication of diabetes mellitus (DM) that very detrimental. Wounds in DFU patient were difficult to be healed so we need some inovation in DFU therapy. Peripheral blood mononuclear cells (PBMNC) therapy showed promising results. This systematic literature review aimed to compare the effectiveness of PBMNC therapy and standard therapy for DFU. Method: This systematic literature review used PRISMA method. Literature searched from Pubmed and Science Direct. Study published in 2010 until 2020. Selected journals conducted quality assessment using JBI Critical Appraisal Tools and then reviewed. Result: Non-surgical sharp debridment (NSSD) and Peripheral blood mononuclear cells (PBMNC) could heal wounds within 6 months. Conclusion: This research was inconclusive. Keywords: Diabetic foot ulcers, mononuclear stem cells, wound healing, debridment